The politics of voicelessness: voices of community elders in ethic and religious minorities in the Philippines - Morales, Sheryl R; Morales, Roque S; Sagun, Randy D (Department of Government Studies, Universitas Muhammadiyah Makassar, 2024)
The study aims to examine the phenomena of minoritization, which involves the imposition of the beliefs and culture of dominant groups onto minority groups, leading to social exclusion and conflicts. The study utilizes data analysis to identify themes related to the process of minoritization. The study illustrates that minoritization occurs when dominant groups perceive themselves as superior and endeavor to dominate others, resulting in violence, oppression, and social exclusion. This study focuses on the perspectives of grassroots voices, going beyond traditional inquiries on equalities between different groups to provide a deeper insight into the systemic challenges encountered by minority communities. It emphasizes attributes such as dominant groups imposing their beliefs on others, perceiving them as inferior, and forcing them to adopt their culture or traditions. To address the issue of minoritization, the study emphasizes the importance of carrying out dialogues at all levels, promoting understanding across various cultures and religions, implementing policies that protect the rights of minority groups, and preventing systematic minoritization. This study enhances broader discussions on inclusivity and equality through exploring its findings in relation to global issues of prejudice. It advocates for the increased recognition and valued of minority voices in society. This emphasizes the need for holistic strategies that promote mutual respect among different communities and prevent conflicts arising from social exclusion.